Oil-mineral flocculation and settling velocity in saline water. (15th April 2020) - Ye, Leiping; Manning, Andrew J.; Hsu, Tian-Jian
Abstract: Cohesive particles in aquatic systems can play an important role in determining the fate of spilled oil via the generation of Oil-Mineral Aggregates (OMAs). Series of laboratory experiments have been conducted aiming at filling the knowledge gap regarding how cohesive clay particles influence the accumulation of petroleum through forming different aggregate structures and their resulting settling velocity. OMAs have been successfully created in a stirring jar with artificial sea-water, crude oil and two types of most common cohesive minerals, Kaolinite and Bentonite clay. With the magnetic stirrer adjusted to 490 rpm to provide a high level homogeneous flow turbulence (Turbulence dissipation ε estimated to be about 0.02 m 2 ⋅s −3 ), droplet OMAs and flake/solid OMAs were obtained in oil-Kaolinite sample and oil-Bentonite sample, respectively. Kaolinite clay with relatively low flocculation rate ( R f  = 0.13 min −1 ) tends to physically attach around the surface of oil droplets. With the lower density of oil, these oil-Kaolinite droplet OMAs generally show lower settling velocity comparing to pure mineral Kaolinite flocs. Differently, Bentonite clay with higher flocculation rate ( R f  = 0.66 min −1 ) produces more porous flocs that can absorb or be absorbed by the oil and form compact flake/solid OMAs with higher density and settling velocity than pure Bentonite flocs. In the mixed Kaolinite-Bentonite sample (1:1 in weight), oil is observed to preferably interacting with Bentonite and increase settling velocity especially in larger floc size classes. Graphical abstract: Image 1 Highlights: Microscopy analysis reveals distinct Oil-Mineral Aggregates (OMA) structures due to clay types. LabSFLOC-2 further reveals the dependence of OMA settling velocity due to structures. Distinct OMA structures & settling velocities are shown to be controlled by mineral stickiness.